Practical Issues of Detaching a New Criminal Case in the Criminal Proceedings of RA - Dilbandyan, Samvel; Melkonyan, Davit (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article is devoted to a discussion of practical issues of detaching a new criminal case provided for by the new Code of Criminal Procedure of the Republic of Armenia. In the article, the author, relying on the opinions expressed in the legal literature, decisions of the Court of Cassation and the European Court, notes that the institution of combining and detaching criminal proceedings cannot be considered as one of the technical means by which the law enforcement agency is able to change, that is, reduce or increase the subject of research on the case in progress. On the contrary, this institution requires a deep and thoughtful approach in its application, since the complex of legal relations regulated by it is in direct connection with the basic, fundamental provisions of the entire criminal process and the tasks facing it.A study of the practice of applying Article 10 of the RA Code of Criminal Procedure shows that its application pursues a different goal that does not follow from the essence of the institution of detaching criminal proceedings. The existing legal practice of detaching criminal proceedings is due to the stipulation in the new Code of Criminal Procedure of the terms of criminal prosecution. If there are several defendants, when they are accused of committing crimes of varying gravity, the body conducting the process, in order not to violate the deadlines for the prosecution, in violation of Article 10 of the Code of Criminal Procedure, separates a proceeding and transfers it to the court. This practice contradicts the meaning of the institution of separation of proceedings and violates the constitutional rights of the accused.
Keywords: separation of proceedings; terms of criminal prosecution; presumption of innocence; impartial court; criminal charge; gravity of the crime; separate proceedings; case law of the ECHR; case law of the Court of Cassation RA; law enforcement practice